Evolutionary history of Trachylepis skinks in the Seychelles islands: introgressive hybridization, morphological evolution and geographic structure. (25th April 2016) - Rocha, Sara; Perera, Anna; Silva, Andreia; Posada, David; Harris, D. James
Abstract : The Seychelles is a remarkably interesting archipelago for evolutionary studies, but only recently have molecular markers been used to explore its biogeographic patterns. Here we used morphological and molecular data to examine diversity and phylogenetic relationships of two endemic skink sister‐species from this archipelago: Trachylepis sechellensis and Trachylepis wrightii . Mitochondrial DNA genealogy rendered a monophyletic T. wrightii nested within a paraphyletic T. sechellensis, whereas nuclear DNA sequences from five unlinked markers reflected the accepted taxonomy. Hybridization and massive mtDNA introgression leading to the complete replacement of the native mtDNA lineage of T. sechellensis in some of the islands were invoked to explain this result, and morphological variation also seemed to reflect this pattern of reticulation. A Mio‐Pliocene divergence between both species is suggested. Multilocus molecular data were used to uncover biogeographic patterns within the archipelago, which reflected shared patterns with other co‐distributed lizard taxa; specifically a north–south marked structure, a close relationship between populations from Fregate and the southern islands, and a detectable isolation within the southern group, between Mahé, and Silhouette and North Islands. Gene flow from these latter islands towards the northern group was also suggested. These results add to the growing body of evidence of the influence of geographic distance and sea‐level oscillations in shaping the genetic structure of Seychellois taxa and of the existence of common biogeographic patterns across the archipelago.